Estudo cristalográfico de berilos naturais - Paula, Renata Layse Gonçalves de (2018)
The crystallography is for excellence the methodology that presents itself as the most adequate for structural elucidation due to the high resolution with which it can be described the electronic density, besides being a methodology that brings with it an interdisciplinary character, crossing the various cognitive areas, corroborating to the state of the art together with the demand for new technologies that come to enter the development of science. In this job are presented the crystallographic studies of 13 crystalline samples of beryl, being 2 samples of acquamarine and 11 industrial beryl, being 1 octahedral sample, in other words, there is a total or partial replacement of Al by some metal, 1 sample in transition from the octahedral type to normal, 3 samples of the normal type, without any type of atomic substitution, 5 transition samples of the normal type for tetrahedra and 2 tetrahedra samples, that is, with total or partial replacement of the Be for Li. Was performed with data sets obtained by X-ray diffraction of monocrystal and complemented with the method of Sum of the Bond Valence Model and Fingerprints. The results showed that through the analysis of the lattice parameters of the samples it was possible to determine the typology of each one through the c/a ratio. Axis a had changes in the 13 diffracted monocrystals, varying between 9,2054Å and 9,2400Å. The c axis showed a slightly more significant variation, its values remained between 9,1791Å and 9,2200Å. The Bond Valence Model was used to indicate possible ions in the structures and their oxidation states. Fingerprints were used to quantify the contribution of each interatomic contact to the stability of the structures. All samples were similar, diverging in small configurations according to the typology and their respective substitutions and inclusions.